2020
DOI: 10.1038/s41598-020-71180-x
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of road dust chemical profiles for source identification and human health impact assessment

Abstract: This study investigated the chemical profiles of fine urban road dust as a set of indicators for major air pollutants at sampling sites or as proxies for potential human health impacts. We examined the chemical compositions of fine particles (< 100 μm) or re-suspended ultrafine particles (< 2.5 μm) in the urban road dust collected from the cities with major emission sources of CO, NH 3 , NO x , PM 2.5 , SO x , and volatile organic compounds. The elemental compositions, including metal contents and volatile or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
3
5
0
Order By: Relevance
“…Road dust. This factor makes a major contribution to crustal species, such as Na + , Al and Fe (60%, 48% and 34% of species in this factor respectively) suggesting this factor may represent the characteristics of a dust related source as reported previously (Kim and Koh, 2020). In addition, the given factor also included significant contributions to Mn, Pb and Zn (26%, 23% and 20% of species in this factor respectively), which are associated with brake and tyre wear as mentioned above (Pant and Harrison, 2012;Pant and Harrison, 2013;Grigoratos and Martini, 2015;Piscitello et al, 2021).…”
Section: Traffic Emissionssupporting
confidence: 71%
“…Road dust. This factor makes a major contribution to crustal species, such as Na + , Al and Fe (60%, 48% and 34% of species in this factor respectively) suggesting this factor may represent the characteristics of a dust related source as reported previously (Kim and Koh, 2020). In addition, the given factor also included significant contributions to Mn, Pb and Zn (26%, 23% and 20% of species in this factor respectively), which are associated with brake and tyre wear as mentioned above (Pant and Harrison, 2012;Pant and Harrison, 2013;Grigoratos and Martini, 2015;Piscitello et al, 2021).…”
Section: Traffic Emissionssupporting
confidence: 71%
“…As many of these components are highly correlated within the panels of PM tested, this method has inherent limitations. However, several studies augmented this observational approach through inhibition of component-specific biological pathways (metal handling, , aryl hydrocarbon receptor mediated xenobiotic metabolism, toll-receptor mediated responses to PM associated biological components or PM fractionation).…”
Section: Toxicology/mechanistic Datamentioning
confidence: 99%
“…Elemental compositions of road dust were analysed (Table S1 †). Previous studies 25,26 have shown that road dust contains various chemical compounds, including organic carbons, sulfur compounds, metals and ions. These studies showed that metal compositions and the relative abundance of hydrocarbons have positive correlations with cytotoxicity and that the chemical prole of road dust may be used as a proxy for assessing human health impacts.…”
Section: Elemental Compositions Of Road Dustmentioning
confidence: 99%